PENGARUH INVESTASI PADA INDUSTRI KECIL FORMAL DAN PADA INDUSTRI KECIL NON FORMAL TERHADAP SUATU PRODUK DOMESTIK REGIONAL BRUTO DI KABUPATEN ACEH UTARA - Ratna Ratna; Devri Sandi Hutabarata (Jurnal Ekonomi Regional Unimal, 2020)
This study aims to determine the effect of investment in formal and non-formal small industries on gross regional domestic products in North Aceh Regency. The data used in this study are secondary data from 2010-2016 with interpolation of data with 84 data. The data analysis method used in this study is multiple linear regression method. The results of the research partially indicate that investment in formal small industries and non-formal small industries has a positive effect on gross regional domestic product in North Aceh District. This means increasing non-formal small industry investment will increase gross regional domestic product in North Aceh Regency. Based on the results of tests carried out simultaneously or together the variables of formal small industry investment and non-formal small industry investment simultaneously influence (in month 3) on the gross regional domestic product in North Aceh District, and the magnitude of the influence of the formal small industry investment variable and investment Non-formal small industry on gross regional domestic product in North Aceh Regency is 0.984, and the remaining 0.0884 is influenced by other variables outside this model.Keywords: Formal Small Industry Investment, Non-Formal Small Industry    and Gross Regional Domestic Product